2017
DOI: 10.1038/cddis.2017.47
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of liver regeneration via myeloid PTEN deficiency

Abstract: Molecular mechanisms that modulate liver regeneration are of critical importance for a number of hepatic disorders. Kupffer cells and natural killer (NK) cells are two cell subsets indispensable for liver regeneration. We have focused on these two populations and, in particular, the interplay between them. Importantly, we demonstrate that deletion of the myeloid phosphatase and tensin homolog on chromosome 10 (PTEN) leading to an M2-like polarization of Kupffer cells, which results in decreased activation of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…[ 11 , 12 ] For instance, phosphatase and tensin homologue deleted on chromosome 10, 10q23.3 KO in macrophages has been reported to promote reparative macrophage polarization and exert proregenerative effects after 70% PHx. [ 29 ] In addition, LR and recovery of liver function are accelerated significantly when reparative bone‐marrow–derived macrophages (BMDMs) are infused into hepatectomized mice. [ 13 ] However, the underlying mechanism in which reparative macrophages affected LR were not clearly shown.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 , 12 ] For instance, phosphatase and tensin homologue deleted on chromosome 10, 10q23.3 KO in macrophages has been reported to promote reparative macrophage polarization and exert proregenerative effects after 70% PHx. [ 29 ] In addition, LR and recovery of liver function are accelerated significantly when reparative bone‐marrow–derived macrophages (BMDMs) are infused into hepatectomized mice. [ 13 ] However, the underlying mechanism in which reparative macrophages affected LR were not clearly shown.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, scientists have researched the interplay between them in the hope of better outcomes for chronic liver diseases. Ma et al 110 demonstrated that the deletion of phosphatase and tensin homolog (PTEN), originally identified as a tumor-suppressor protein, could activate the M2 polarization of Kupffer cells, leading to the less activated phenotype of NK cells, probably through direct cell-cell contact or decreased secretion levels of IL12 and IL15. Furthermore, PTEN-deficient Kupffer cells secreted more growth factors required for liver regeneration, 110 identifying PTEN as a potential target for liver regeneration.…”
Section: Therapies Improve Liver Regeneration Based On Innate Immune ...mentioning
confidence: 99%
“…Ma et al 110 demonstrated that the deletion of phosphatase and tensin homolog (PTEN), originally identified as a tumor-suppressor protein, could activate the M2 polarization of Kupffer cells, leading to the less activated phenotype of NK cells, probably through direct cell-cell contact or decreased secretion levels of IL12 and IL15. Furthermore, PTEN-deficient Kupffer cells secreted more growth factors required for liver regeneration, 110 identifying PTEN as a potential target for liver regeneration. For NK cells, they have been previously proved to be beneficial for attenuating inflammation and preventing adverse cardiac remodeling via the cell crosstalk with allogeneic human cardiac-derived progenitor cells, 111 implying their potential roles in LPLC-induced liver regeneration.…”
Section: Therapies Improve Liver Regeneration Based On Innate Immune ...mentioning
confidence: 99%
“…PTEN-mediated AKT/β-catenin signaling controls inflammatory damage in mouse liver triggered by ischemia/reperfusion injury and regulates the release of inflammatory cytokines in the liver 31 . Meanwhile, PTEN regulates NK cells and Kupffer cells in the liver to modulate the proliferation of hepatocytes to promote liver repair 32 . However, the role of PTEN in Lgr5+ hepatocytes mediated liver regeneration remains to be explored.…”
Section: Introductionmentioning
confidence: 99%